1997
DOI: 10.1111/j.1365-2621.1997.tb04378.x
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Stability of Invertase in Reduced‐Moisture Amorphous Matrices in Relation to Glassy State and Trehalose Crystallization

Abstract: The thermal stability of enzyme invertase in reduced-moisture model systems of maltodextrin (MD), polyvynilpyrrolidone (PVP; MW 40,000) and trehalose heated at 90ЊC was studied. Significant invertase inactivation was observed in heated glassy PVP and MD systems kept well below their glass transition temperature (T g ), but the enzyme was fairly stable in rubbery trehalose systems. However, at moisture contents which allowed trehalose crystallization rapid thermal inactivation of invertase was observed. Inverta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
75
2
1

Year Published

1997
1997
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 103 publications
(86 citation statements)
references
References 36 publications
8
75
2
1
Order By: Relevance
“…It was suggested that the high glass transition temperature of trehalose may lead to formation of a glassy matrix during cooling, preventing its crystallization. This vitrification hypothesis alone, however, may not be sufficient to explain why trehalose may remain soluble in the winter hemolymph because the solubility of trehalose in actual hemolymph would be lower than that in water (as the water activity is lower in such a complex system) and the winter temperatures typically fluctuate considerably over the winter, but are often higher than the glass transition temperature (9,(32)(33)(34)(35). Such phase transitions of the hemolymph components are a potential cause of low temperature damage in freeze-avoiding insects (36).…”
Section: Resultsmentioning
confidence: 99%
“…It was suggested that the high glass transition temperature of trehalose may lead to formation of a glassy matrix during cooling, preventing its crystallization. This vitrification hypothesis alone, however, may not be sufficient to explain why trehalose may remain soluble in the winter hemolymph because the solubility of trehalose in actual hemolymph would be lower than that in water (as the water activity is lower in such a complex system) and the winter temperatures typically fluctuate considerably over the winter, but are often higher than the glass transition temperature (9,(32)(33)(34)(35). Such phase transitions of the hemolymph components are a potential cause of low temperature damage in freeze-avoiding insects (36).…”
Section: Resultsmentioning
confidence: 99%
“…Variations in chemical stability that do not seem to be related to global mobility have also been observed for various solid proteins, including restriction enzyme EcoRI dried with sucrose, trehalose, maltodextrin or PVP, 104 lactase and invertase lyophilized with trehalose, maltose, lactose, sucrose, raffinose, maltodextrin, casein or PVP, 22,[105][106][107][108] and glucose-6-phosphate dehydrogenase lyophilized with dextran, sucrose or raffinose. [109][110] It is not easy to explain the lack of correlation between chemical stability and global mobility for proteins because of many complicated factors possibly affecting the chemical stability.…”
Section: Examples For Chemical Stability Not Apparently Related To Glmentioning
confidence: 96%
“…[6][7][8] Hence, storage of proteins at temperatures above T g increases the molecular mobility in the dried sample, which can foster degradative chemical reactions and/or protein aggregation in the dried sample. 2,3,9,10 However, molecular mobility in glasses has also been demonstrated at temperatures as low as 50 degrees below T g , on a pharmaceutically relevant time scale of months. 11 Even with storage below T g , protein degradation may still occur at unacceptable levels.…”
Section: Introductionmentioning
confidence: 96%
“…Dried proteins and stabilizing additives are amorphous. [2][3][4][5] Degradation of proteins in formulations stored at temperatures below T g is restricted by the extremely high viscosity of the glassy state. During warming, amorphous solids undergo a characteristic glass to rubber transition at a temperature (glass transition temperature, T g ) that depends on the composition of the amorphous phase.…”
Section: Introductionmentioning
confidence: 99%